1994
DOI: 10.1002/humu.1380030405
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis patients from the black sea region: The 1677delTA mutation

Abstract: A 2 bp deletion in exon 10 of the CFTR gene, 1677delTA, which is very rare among CF chromosomes worldwide, was found to be a relatively common cause of cystic fibrosis in countries located in the region of the Black Sea. The frequency of the mutation was compared among cystic fibrosis patients from several populations, namely Bulgarians, Turks, Greek-Cypriots, Georgians, and Russians. The deletion is most common among Georgian CF patients and gradually declines in frequency in neighbouring populations. It is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…A few other mutations in CFTR are present at high frequency in specific subpopulations (e.g. W1282X in Ashkenazi Jews (Kornreich et al 2004) and 1677delTA around the Black Sea (Angelicheva et al 2005)). The high rate of CF carriers has led to speculation that there must be, similar to the sickle cell haemoglobin (HbS) advantage in malaria, a selective advantage for CF heterozygotes.…”
mentioning
confidence: 99%
“…A few other mutations in CFTR are present at high frequency in specific subpopulations (e.g. W1282X in Ashkenazi Jews (Kornreich et al 2004) and 1677delTA around the Black Sea (Angelicheva et al 2005)). The high rate of CF carriers has led to speculation that there must be, similar to the sickle cell haemoglobin (HbS) advantage in malaria, a selective advantage for CF heterozygotes.…”
mentioning
confidence: 99%
“…The probands of families 2801 and 2802 that we report here were first identified as being carriers of AF508 and 1677delTA respectively (Constantinou-Deltas et al 1992;Angelicheva et al 1993). Both are severe mutations that affect significantly the function of the protein Ivaschenko et al 1991;Tsui 1992;Angelicheva et al 1993), with symptoms in the lungs and the pancreas. And yet neither of our patients had these severe symptoms.…”
Section: Discussionmentioning
confidence: 77%
“…Patient 4457 of family 2801 is nearly 6 years old with no pancreatic insufficiency and without unusually frequent chest infections (Table 1). Patient 5292 of family 2802 is 15 months old and is doing well except for slight growth delay and occasional electrolyte disturbances (Angelicheva et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, no other CFTR mutation is expected. Several genotype-phenotype studies including the CF genotype-phenotype consortium have shown that there are mutations like the ⌬F508, 2,6,11 W1282X, 3,6 G542X, 6 N1303K, 4,6 and R533X 5,6 in which Ͼ95% of the patients had PI [2][3][4][5][6][7][8][9][10] whereas others like the 3849ϩ10kb C-ϾT, …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies analyzed the genotype-phenotype correlation in several mutations for which a large enough number of patients was available. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] These studies have shown that genetic factors influence the severity of the disease, and that there are two groups of mutations. One group is associated with pancreatic insufficiency (PI) (Ͼ95% of cases) and a young age at diagnosis (usually Ͻ1 year of age), high sweat chloride levels (Ͼ80 meq/L), and meconium ileus (20% to 30% of the cases).…”
mentioning
confidence: 99%